Re-Cording Lives Governing Asylum in Switzerland and the Need to Resolve - Pörtner, Ephraim (Sozial- und Kulturgeographie, 2021)
Administrative asylum procedures are permeated by tensions between rationalities of legality, efficiency, and deterrence in asylum casework and their various effects on cases. Based on ethnographic research in the Swiss asylum administration, this book unveils the pragmatics and politics of rendering asylum cases resolvable by re-cording the lives of applicants in terms of asylum. With his reading of power and agency in administrations, Ephraim Pörtner offers a critical view of the intricate relationship between practices of asylum casework and the governmental need to resolve claims of people seeking protection.